394 CA125 normalization following neoadjuvant chemotherapy complementing the chemotherapy response system in the prognostication of patients with high-grade serous ovarian carcinoma. (13th November 2020) - Li, J; Wu, M; Wang, L; Lin, Z
Abstract : Objective: To investigate whether CA125 normalization following neoadjuvant chemotherapy (NACT) can complement the chemotherapy response system (CRS) in the prognostication of patients with tubo-ovarian high-grade serous carcinoma (HGSC). Methods: In total, 106 HGSC patients who received NACT followed by interval debulking surgery (IDS) for FIGO stage IIIC-IV disease were included, and their clinical data were retrospectively reviewed. The primary endpoint was progression-free survival (PFS). Cox regression analysis was performed to identify predictors of PFS. Results: Following NACT, CRS3 was noted in 24 patients (22.6%), and CA125 normalization (≤ 35 U/ml) was noted in 54 patients (50.9%). Both CRS3 and CA125 normalization were identified as independent prognosticators of PFS. Combining these two factors, we stratified the 106 patients into three groups with different risks of recurrence: low-risk group (CRS3 + post-NACT CA125≤ 35 U/ml; n = 17, 16.0%), intermediate-risk group (CRS3 + post-NACT CA125 > 35 U/ml; n = 7, 6.6%) and high-risk group (CRS1-2; n= 82, 77.4%). The differences in PFS between the three groups were significant (log-rank test, P < 0.0001). In Cox regression analyses, the new stratification method was found to have an independent prognostic effect. Conclusion: Both the CRS system and the normalization of CA125 following NACT could reliably predict the risk of recurrence following primary treatment. The combination of the two factors refined the prognostic stratification of HGSC patients who were treated with NACT and IDS.